Research on Relationship Between Runoff of Upper Reaches of the Yellow River and Sea Surface Temperature and Atmospheric Circulation Characteristics - WANG Dan; PAN Hongzhong; BAI Yu (Renmin Zhujiang)
Precipitation in any watershed is a part of the global atmosphere and water cycle.Most of the water in the atmosphere comes from seawater evaporation.The amount of water vapor is directly related to the sea surface temperature (SST),which is the main driving factor of water cycle.It is a very complicated process that seawater evaporates into the atmosphere,and the water in the atmosphere falls on a certain watershed and forms runoff.In order to increase the forecast period of runoff,the teleconnection relationship between SST and runoff has attracted more and more attention.By using the natural orthogonal function decomposition method and correlation analysis,this paper establishes the correlation between the runoff in the upper reaches of the Yellow River and the corresponding sea surface temperature,and then verifies and analyzes the formation mechanism from the perspective of atmospheric circulation.The results show that the change of sea surface temperature is closely related to the runoff of upper reaches of Yellow River in flood season.